Targeted overexpression of endothelial nitric oxide synthase in endothelial cells improves cerebrovascular reactivity in Ins2Akita-type-1 diabetic mice. Issue 6 (June 2016) - Chandra, Saurav B; Mohan, Sumathy; Ford, Bridget M; Huang, Lei; Janardhanan, Preethi; Deo, Kaiwalya S; Cong, Linlin; Muir, Eric R; Duong, Timothy Q
Reduced bioavailability of nitric oxide due to impaired endothelial nitric oxide synthase (eNOS) activity is a leading cause of endothelial dysfunction in diabetes. Enhancing eNOS activity in diabetes is a potential therapeutic target. This study investigated basal cerebral blood flow and cerebrovascular reactivity in wild-type mice, diabetic mice (Ins2 Akita+/− ), nondiabetic eNOS-overexpressing mice (TgeNOS), and the cross of two transgenic mice (TgeNOS-Ins2 Akita+/− ) at six months of age. The cross was aimed at improving eNOS expression in diabetic mice. The major findings were: (i) Body weights of Ins2 Akita+/− and TgeNOS-Ins2 Akita+/− were significantly different from wild-type and TgeNOS mice. Blood pressure of TgeNOS mice was lower than wild-type. (ii) Basal cerebral blood flow of the TgeNOS group was significantly higher than cerebral blood flow of the other three groups. (iii) The cerebrovascular reactivity in the Ins2 Akita+/− mice was significantly lower compared with wild-type, whereas that in the TgeNOS-Ins2 Akita+/− was significantly higher compared with the Ins2 Akita+/− and TgeNOS groups. Overexpression of eNOS rescued cerebrovascular dysfunction in diabetic animals, resulting in improved cerebrovascular reactivity. These results underscore the possible role of eNOS in vascular dysfunction in the brain of diabetic mice and support the notion that enhancing eNOS activity in diabetes is a potential therapeutic target.